Art and the community in the Philippines: Conversation between Sarena Abdullah and Eileen Legaspi-Ramirez - Abdullah, Sarena; Legaspi-Ramirez, Eileen (Intellect, 2018)
an artist might choose to make their art outside the typical gallery/museum space but may not be wholly interested in the participative aspect of doing work in collaboration and subject to community processes. On the other end of the spectrum would be artists working with communities/those explicitly aligning their practices with community engagement, and where the art might actually take a backseat to the processes of immersion and organizing. Another useful distinction could also be made: artists coming into a community setting with the expressed purpose of making art on site, and those artists more explicitly wishing to situate their practice within communities